COVID-19 and Student Well-Being: Stress and Mental Health during Return-to-School - Schwartz, Kelly Dean; Exner-Cortens, Deinera; McMorris, Carly A.; Makarenko, Erica; Arnold, Paul; Van Bavel, Marisa; Williams, Sarah; Canfield, Rachel (Canadian journal of school psychology, 2021)
Students have been multiply impacted by the COVID-19 pandemic: threats to their own and their family’s health, the closure of schools, and pivoting to online learning in March 2020, a long summer of physical distancing, and then the challenge of returning to school in fall 2020. As damaging as the physical health effects of a global pandemic are, much has been speculated about the “second wave” of mental health crises, particularly for school-aged children and adolescents. Yet, few studies have asked students about their experiences during the pandemic. The present study engaged with over two thousand (N = 2,310; 1,288 female; Mage = 14.5) 12- to 18-year-old Alberta students during their first few weeks of return-to-school in fall 2020. Students completed an online survey that asked about their perceptions of COVID-19, their fall return-to-school experiences (84.9% returned in-person), their self-reported pandemic-related stress, and their behavior, affect, and cognitive functioning in the first few weeks of September. The majority of students (84.9%) returned to school in person. Students reported moderate and equal concern for their health, family confinement, and maintaining social contact. Student stress levels were also above critical thresholds for 25% of the sample, and females and older adolescents (age 15–18 years) generally reported higher stress indicators as compared to males and younger (age 12–14 years) adolescents. Multivariate analysis showed that stress indicators were positively and significantly correlated with self-reported behavioral concerns (i.e., conduct problems, negative affect, and cognitive/inattention), and that stress arousal (e.g., sleep problems, hypervigilance) accounted for significant variance in behavioral concerns. Results are discussed in the context of how schools can provide both universal responses to students during COVID-19 knowing that most students are coping well, while some may require more targeted strategies to address stress arousal and heightened negative affect.